2021
DOI: 10.3390/md19040182
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Upregulate SIRT1/3, Activate PGC-1α via Deacetylation, and Induce Nrf1 Production in 5/6 Nephrectomy Rat Model

Abstract: Mitochondrial dysfunction contributes to the pathogenesis of kidney injury related with cardiovascular disease. Peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) protects renal tubular cells by upregulating nuclear factor erythroid 2-related factor 2 (Nrf2). AMP-activated protein kinase (pAMPK)-mediated phosphorylation and sirtuin 1/3 (SIRT1/3)-mediated deacetylation are required for PGC-1α activation. In the present study, we aimed to investigate whether omega-3 fatty acids (FAs) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…SIRT1 and SIRT3 are crucial coordinators of PGC-1α, adjusting the biogenesis and function of the mitochondria (47). FOXO1 and FOXO3 bind to the PGC-1α promoter and enhance its transcription (48). We found that the Mo and/or Cd treatment observably decreased both the mRNA and protein levels of PGC-1α, and markedly reduced the mRNA levels of SIRT1, SIRT3, FOXO1 and FOXO3.…”
Section: Discussionmentioning
confidence: 69%
“…SIRT1 and SIRT3 are crucial coordinators of PGC-1α, adjusting the biogenesis and function of the mitochondria (47). FOXO1 and FOXO3 bind to the PGC-1α promoter and enhance its transcription (48). We found that the Mo and/or Cd treatment observably decreased both the mRNA and protein levels of PGC-1α, and markedly reduced the mRNA levels of SIRT1, SIRT3, FOXO1 and FOXO3.…”
Section: Discussionmentioning
confidence: 69%
“…Sirt3-KO mice showed lower palmitate oxidation, lower respiratory capacity, lower ATP synthesis, and abnormal lipid accumulation, with impaired mitochondrial and contractile cardiac function ( Chen T. et al, 2015 ; Koentges et al, 2015 ). Finally, low SIRT-3 levels are also correlated with a down-regulation of PGC1-α ( Yu et al, 2017 ), suggesting the conservation of the reported PGC-1α/SIRT3 protective axis ( Son et al, 2021 ) due to SIRT3 enhanced activity ( Figure 3 ). Thus, all the listed findings highlight the importance of elucidate the hypothetical ERα or ERRs-SIRT3-mtUPR mitochondrial cardioprotective pathway in different CVDs as a new important axis in the cardioprotection triggered by estrogens.…”
Section: Non-classical Pathways and Mitochondrial To Nucleus Communic...mentioning
confidence: 88%
“…Additionally, breast milk is an excellent source of omega 3 for newborn infants ( Berenhauser et al, 2012 ; Samuel et al, 2020 ). The positive effect of omega 3 fatty acids is largely attributed to PGC-1α activation through the SIRT1/3 pathways ( Son et al, 2021 ). Omega 3 fatty acids are essential for brain and retinal development during the postnatal period and decreased levels are associated with increased risk for neonatal morbidities such as respiratory disease, decline in cognitive and motor abilities, and decreased postnatal growth ( Martin et al, 2011 ; Bernardi et al, 2012 ; Fink et al, 2016 ; Lapillonne and Moltu, 2016 ; Gould et al, 2018 ).…”
Section: Therapeutic Agents That Can Regulate Pgc-1α Activitymentioning
confidence: 99%
“…Limited studies have investigated the mechanism for the protective effect of omega 3 supplementation. However, recent studies report that it rescues PGC-1α, SIRT1/3, NRF-1/2, and AMPK protein expression in nephrectomy rats, and significantly increases total mitochondrial content in rodent skeletal muscle tissue and human skeletal muscle cells ( Vaughan et al, 2012 ; Liu et al, 2019b ; Son et al, 2021 ). Omega 3 fatty acids are safe and well-tolerated orally in infants and children hence, further mechanistic studies exploring its effect on PGC-1α signaling in the brain and lung during development would enhance our understanding of the therapeutic potential in preterm infants.…”
Section: Therapeutic Agents That Can Regulate Pgc-1α Activitymentioning
confidence: 99%